Pendidikan Konservasi dalam Mengembangkan Karakter Peduli Lingkungan Anak Sekolah SD Negeri Wonodri Semarang - Kusuma, Ayu Rahayu; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Contemporary challenges in human ecosystems have developed into global crises, endangering the well-being of humanity. At the same time, environmental changes around the world have prompted introspection regarding the interactions between humans and the ecological environment. Environmental management in this context is a manifestation of ethos or behavior regarding a person's obligation to protect, respect and preserve nature. It encapsulates a broad spectrum of attitudes towards environmental integrity, which translate into actions aimed at improving and maintaining environmental health in all aspects of interaction with nature. Qualitative methodology underlies this research effort. The data collection methodology used includes documentation and literature review. The latter involves searching a variety of written sources including books, archives, periodicals, articles, journals and related documents. These efforts are directed at fostering an environmentally conscious attitude among elementary school students through scholastic activities.